Mitigation of power quality issues using UPQC with STF-SRF technique under adverse voltage source condition / Muhammad Alif Mansor ... [et al.] - Mansor, Muhammad Alif; Othman, Muhammad Murtadha; Musirin, Ismail; Mohammad Noor, Siti Zaliha (Universiti Teknologi MARA, 2021)
A three-phase three-wire of Unified Power Quality Conditioner (UPQC) is used to compensate for the power quality issues that exist in the point of common coupling (PCC) on the microgrid (MG) of the power system and the harmonics penetrated by the non-linear loads. This paper presents an amalgamation of a self-tuning filter (STF) with synchronous reference framework (SRF) of direct-quadrature-zero (dq0) fundamental based on UPQC to enhance power quality at the PCC under adverse voltage source condition (unbalanced and distorted source voltage). The modified SRF technique integrated the self-tuning filter (STF) with the unit vector generator (UVG) technique for designing the control phase synchronization algorithm of UPQC. Therefore, a phase-locked loop (PLL) necessity is omitted. The STF-UVG is used to produce the synchronization phases reference which can lead to UPQC controller generated reference current and voltage in phase with the operating power system. The suggested STF-SRF technique is compared with the traditional SRF technique by considering several case scenarios of source voltage in MATLAB-Simulink software are discussed in detail.